2021
DOI: 10.1177/0956462420973106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of people living with HIV hospitalized with COVID-19: a nationwide experience

Abstract: In this prospective, multicentric, observational study, we describe the clinical characteristics and outcomes of people living with HIV (PLHIV) requiring hospitalization due to COVID-19 in Chile and compare them with Chilean general population admitted with SARS-CoV-2. Consecutive PLHIV admitted with COVID-19 in 23 hospitals, between 16 April and 23 June 2020, were included. Data of a temporally matched-hospitalized general population were used to compare demography, comorbidities, COVID-19 symptoms, and major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
(30 reference statements)
0
42
0
Order By: Relevance
“…A total of 3,344 articles were retrieved from electronic databases up to 9 March 2021. After the removal of irrelevancy and duplicates, 83 articles were taken for fulltext screening, and, finally, 14 studies providing outcomes of interest were included for review [4,5,[13][14][15][16][17][18][19][20][21][22][23][24]. Of these included studies 13 were peer-reviewed, while 1 case series was unpublished [19].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 3,344 articles were retrieved from electronic databases up to 9 March 2021. After the removal of irrelevancy and duplicates, 83 articles were taken for fulltext screening, and, finally, 14 studies providing outcomes of interest were included for review [4,5,[13][14][15][16][17][18][19][20][21][22][23][24]. Of these included studies 13 were peer-reviewed, while 1 case series was unpublished [19].…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 1 outlines the characteristics and data extracted from the included studies. Nine studies were of cohort design [4,5,13,15,17,18,[20][21][22] and the other five were case series [14,16,19,23,24]. Only one cohort study used matched population design while comparing PLWHA and non-PLWHA [21].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such retrospective study leads to a understanding that irrespective of HIV status, patients with COVID-19 still have low counts of CD4+ T cells. However, some studies reported poorer COVID-19 related outcomes in patients living with HIV ( Ceballos et al, 2021 ; Tesoriero et al, 2021 ). The divergent findings in the case of HIV–SARS-CoV-2 co-infection warrant a thorough investigation into the immunological aspects of SARS-CoV-2 co-infection with HIV.…”
Section: Introductionmentioning
confidence: 99%